EYESHADOW DARI LIOFILISAT MESOKARP BUAH NAGA MERAH DAN MESOKARP BUAH MANGGIS - Maria Ulfa; Besse Hardianti (Universitas Islam Negeri Alauddin Makassar, 2017)
Eyeshadow is a decorative cosmetic whose active ingredient is dyestuff. The dye consists of synthetic dyes and natural dyes. Synthetic substances in the long term can disrupt the respiratory organs, liver and are carcinogenic, so the selection of natural dyes is more profitable. Natural dyes can be taken from plants, minerals and animals. The purpose of this research is to utilize the skin waste of mesokarp part of red dragon fruit and mangosteen fruit skin with anthocyanin content which can be used as a dye in cosmetics. First stage The mesocarp sample of dragon fruit skin and mangosteen peel is extracted with aquadest solvent and citrate buffer with a ratio of 5: 1, then concentrated and in freeze drying until lyophilisate is obtained. The second stage is made by adding lyophilisate and other additives to produce Eyeshadow formula. The final stages are stability evaluation such as accelerated storage test, organoleptis, homogeneity, adhesion, dispersion, viscosity, pH, color dispersion test and then test irritation. The results showed that extract of mesokarp liofilisiat super red dragon fruit and liofilisat of mangosteen produce dye from anthocyanin which can be formulated into Eyeshadow, the higher the concentration of extract hence the sharper the resulting color. Eyeshadow produced from super red dragon fruit mesokarp and mangosteen produce an irritation index of 0.04-0.99